1995
DOI: 10.1104/pp.107.4.1433
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid and Its Positional Isomer, cis-Vaccinic Acid, in the Appendix of Sauromatum guttatum during Anthesis

Abstract: California 9561 6 (E.R.S.); and Fairchild Tropical Garden, l h e fatty acid profiles of various organs of the thermogenic inflorescence of Sauromatum guttatum and of the sporophylls of thermogenic male cones of two cycad species (fncephalartos ferox and Dioon edule var edule and var angustifolium) were determined by gas chromatography. During anthesis, palmitate (1 6:0), oleate [18:1 (9)], cis-vaccinate [18:1 (ll)], and linoleate [18:2 (9, 12)l were the most abundant fatty acids i n the Sauromatum appendix.cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These pockets accumulate terpenes that stay in these pockets until D-day, the day of heatproduction, when they are liberated to the atmosphere (Skubatz et al, 1995a). In the present paper we demonstrate that the interaction between the endoplasmic reticulum and the plasma membrane is very complex and that it seems to form additional new excretory pathways of volatiles.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…These pockets accumulate terpenes that stay in these pockets until D-day, the day of heatproduction, when they are liberated to the atmosphere (Skubatz et al, 1995a). In the present paper we demonstrate that the interaction between the endoplasmic reticulum and the plasma membrane is very complex and that it seems to form additional new excretory pathways of volatiles.…”
Section: Introductionsupporting
confidence: 51%
“…Therefore, this structure might be involved in the breakdown of triglycerides stored in the lipid bodies (Murphy, 1990) to volatiles. We have shown that on D-day the amount of lipids decreases dramatically (Skubatz et al 19956) and this decrease might contribute to the release of lipidic volatiles. The presence of free fatty acids in the volatile mixture supports our conclusion that the conversion of fattj' acids to volatiles is carried out at the periphery of the cell, so that these volatiles can be discharged immediately upon production.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations